The impact of lymph vascular space invasion on recurrence and survival in patients with early stage endometrial cancer. (23rd September 2013) - Loizzi, V.; Cormio, G.; Lorusso, M.; Latorre, D.; Falagario, M.; Demitri, P.; Scardigno, D.; Selvaggi, L.E.
<x xml:space="preserve">Abstract</x> The aim of this study was to determine impact of lymph vascular space involvement (LVSI) on recurrence and survival in early stage of endometrial cancer. From 1991 through 2010, all endometrial cancer patients at University Hospital of Bari, Italy were identified. The Log‐rank test and Kaplan–Meyer methods were used for time‐to‐event analysis to evaluate the effects of on lymph vascular space involvement recurrence rate and survival time. Of the 560 endometrial cancer patients, 525 underwent primary surgery. Of those, 399 had early stage disease. Three hundred and forty women were not found to have LVSI, whereas 59 were found to have lymph vascular space involvement. Forty‐nine (12%) patients developed a recurrence and 20 of them showed lymph vascular space involvement. The statistical analysis demonstrated that LVSI was strongly associated with a poor survival (P < 0.0001). Lymph vascular space involvement is associated with a high risk of recurrence and poor overall survival in early stage of endometrial cancer; therefore, the clinical decision to decide whether or not a patient with early stage endometrial cancer should receive adjuvant therapy should be included the evaluation of lymph vascular space involvement.